Pemberdayaan Ekonomi Masyarakat Ala Pondok Pesantren di Kelurahan Kejawan Putih Tambak Surabaya - Syahrul Falah; Irham Zaki (Universitas Airlangga, 2017)
This research is aim to describe the role of Islamic Boarding School of Hidayatullah Surabaya in empowering community economic activity around it. This research is using qualitative approach with study case strategy. Analitical technique is based on theoritical preposition, that followed the theoritical preposition which guide the case of study. Validation technique of data is using sources triangulation technique, which is examine the credibillity of data by crosschecking it within several sources. Data collecting is conducted by interviews, observation, and documentation. The result of this research show there is a role of Islamic Boarding School Hidayatullah for empowering the economic activity of the communnity among the area, which is creating job opportunities; creating an partnership between Islamic boarding school and coummunity around it; a social responsibility showed by counseling, training, and accompaniment activities doing by the islamic boarding school to the community members which are needed.